The role of social protection of pharmacies and social satisfaction of pharmacy visitor (International Journal of Scientific Research and Management (IJSRM), 2022)
The modern pharmaceutical industry is becoming one of the fastest growing areas in the industry. The main task of pharmacies at the present stage of economic development is not only to make a profit, but, first of all, to perform a social function in providing high-quality and affordable medicines to the population of the country. Since pharmacy has a social orientation, special attention is paid to the issue of forming an assortment of drugs, taking into account the solvency of the population and optimizing the provision of certain pharmaceutical remedies. It has been proven that a well-formed assortment of drugs and medical devices increases the rate of inventory turnover, which significantly affects the efficiency of a pharmacy.